The Hobbit (The Lord of the Rings #0) - J.R.R. Tolkien (Ireland HarperCollins Publisher, 2006)
Smaug certainly looked fast asleep, when Bilbo peeped once more from the entrance. He was just about to step out on to the floor when he caught a sudden thin ray of red from under the drooping lid of Smaug's left eye. He was only pretending to be asleep! He was watching the tunnel entrance... Whisked away from his comfortable, unambitious life in his hobbit-hole in Bag End by Gandalf the wizard and a company of dwarves, Bilbo Baggins finds himself caught up in a plot to raid the treasure hoard of Smaug the Magnificent, a large and very dangerous dragon...
Keywords: Adventure; Classics; Fiction; Fantasy; Science Fiction